Attitudes toward Physician-Nurse Collaboration in Pediatric Workers and Undergraduate Medical/Nursing Students - Yong Wang; Yong-fang Liu; Hao Li; Tingyu Li (Behavioural Neurology)
The purpose of this study was to compare the attitudes of pediatric workers and undergraduate medical/nursing students toward collaboration. Attitude toward collaboration was measured using an adaptation of the Jefferson Scale of Attitude toward Physician-Nurse Collaboration. The 656 questionnaires were gathered from pediatrician, pediatric interns, and medical students (PIS) and pediatric nurses, nursing interns, and nursing students (NIS). Results showed a statistically significant difference in the total mean scores in attitudes towards collaboration with NIS scoring higher. Among the participants of PIS, the pediatricians obtained the highest mean scores, while, among the participants of NIS, the pediatric nurses got higher mean scores than nursing interns. It is desirable that medical and nurse schools should include interprofessional education in their curriculum to increase the understanding of the complementary roles of physicians and nurses and to encourage establishment of an interdependent relationship between them.